2013
DOI: 10.1007/s10597-013-9599-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived School Safety is Strongly Associated with Adolescent Mental Health Problems

Abstract: School environment is an important determinant of psychosocial function and may also be related to mental health. We therefore investigated whether perceived school safety, a simple measure of this environment, is related to mental health problems. In a population-based sample of 11,130 secondary school students, we analysed the relationship of perceived school safety with mental health problems using multiple logistic regression analyses to adjust for potential confounders. Mental health problems were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…School safety, including freedom from bullying, is an important determinant of physical 24 and mental health. 25,26 Ensuring safe schools may be a key strategy for preventing juvenile offending. Teachers have a profound ability to influence youths.…”
Section: Discussionmentioning
confidence: 99%
“…School safety, including freedom from bullying, is an important determinant of physical 24 and mental health. 25,26 Ensuring safe schools may be a key strategy for preventing juvenile offending. Teachers have a profound ability to influence youths.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of dental pain in Brazilian schoolchildren was higher in areas with low social development, and the distribution of periodontal disease in adolescents varied significantly between schools according to their annual tuitions and fees . Although adolescents’ health has been influenced by specific social environments, including bullying behaviour and physical violence at school, studies addressing these predictors in oral health research are scarce …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role of the school environment in both enabling and reducing rates of aggression and violence is of particular importance. Research demonstrates that the safety and comfort of youth during the school day in the United States is directly related to their quality of health and academic success . Research has increasingly demonstrated the role of a positive school climate in impacting students' health, ability to engage positively with their peers, and their learning process .…”
mentioning
confidence: 99%
“…There is also a strong association between exposure to aggression and violence and poor health and academic outcomes. A perceived lack of school safety is related to both poor mental health and increased victimization by relational aggression . Exposure to aggression of any form contributes directly to the quality of one's mental health and can have extreme and debilitating effects on youth's quality of life .…”
mentioning
confidence: 99%